MR imaging of meniscal tears - Gadgil, Sharad G.; Kakade, Abhay G.; Bagga, Rounak R.; Yadav, Mahesh H.; Patni, Zoya Mohammed Yusuf (International Journal of Research in Medical Sciences, 2017)
Background: Menisci transmit the forces across the joint and cushion the mechanical loading of the joint. Thus, it is important to identify meniscal tear. A thorough understanding of normal meniscal anatomy and surrounding structure is critical for diagnosis. Magnetic resonance imaging is the current modality of choice providing fine resolution and multi-planar imaging for identifying the meniscal injuries and the various pattern of tear, helping to plan the subsequent management. The purpose of the work was to study the role of MRI in classifying the meniscal injuries. Methods: MRI Knee of 136 patients with meniscal injuries was studied. All the MR imaging scans were performed on 1.5-T MR system (Siemens magnetom Essenza). Results: A total of 136 patients were studied in which majority of the patient’s i.e. 90.44 % had medial meniscal tear while 18.38 % patients had lateral meniscal tear. Both medial and lateral meniscal tears were found in 8.82 % patients. Among the different types of tears, horizontal tear was the most common tear in both medial and lateral meniscus comprising 52.8 % and 52 % respectively. The tears being most common in the age group 41-50years. There were associated injuries to the other ligaments of the knee joint along with meniscal tear, ACL tear being the most common and was seen in 50% of patients. Conclusions: MRI is a good modality for classifying meniscal injury and evaluation of injuries to the associated ligaments. Secondary signs are good predictors of underlying meniscal tear in equivocal cases.